2014
DOI: 10.1039/c4em00076e
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of metallothioneins in the earthworm by lomefloxacin–europium(iii) fluorescent probe

Abstract: A new fluorimetric method was established for the determination of trace amounts of metallothioneins (MT) in earthworm, using a lomefloxacin-europium(iii) (LMLX-Eu(3+)) complex as a fluorescent probe. In a pH 6.5 Tris-HCl buffer solution, MT can markedly decrease the fluorescence intensity of LMLX-Eu(3+) at λ = 613 nm, and the magnitude of the decrease in this intensity was in direct proportion to the concentration of MT. The linear range was 0.08-20 mg L(-1) with a detection limit of 0.022 mg L(-1), and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The improvement of fl uorescent technique for MT detection resulted in detecting trace amount of MTs where fl uorescent agents like ammonium-7fl uorobenzo-2-oxa-1, 3-diazole-4-sulfonate (SBD-F) [96] and monobromobimane (mBBr) [97] are derived. Geng, et al [98] further improved on the fl uorimetric method for MT quantifi cation; it was sensitive to a wide range of MT concentrations and gave a relatively accurate estimation of MT. It however required tandem column system to separate the derived compound to eliminate interference or require a prior MT purifi cation before derivation.…”
Section: Methods Of Metallothionein (Mts) Detection and Quantifi Cationmentioning
confidence: 99%
“…The improvement of fl uorescent technique for MT detection resulted in detecting trace amount of MTs where fl uorescent agents like ammonium-7fl uorobenzo-2-oxa-1, 3-diazole-4-sulfonate (SBD-F) [96] and monobromobimane (mBBr) [97] are derived. Geng, et al [98] further improved on the fl uorimetric method for MT quantifi cation; it was sensitive to a wide range of MT concentrations and gave a relatively accurate estimation of MT. It however required tandem column system to separate the derived compound to eliminate interference or require a prior MT purifi cation before derivation.…”
Section: Methods Of Metallothionein (Mts) Detection and Quantifi Cationmentioning
confidence: 99%
“…In this latter study, fluorescence analysis indicates that La(III) binds to both metallothioneins via the oxygen atoms of aspartic or glutamic acid residues. A fluorimetric method of quantifying MTs is based on the use of lomefloxacin-europium(III) complex as a fluorescent probe, since MT reacts with the LMLX-Eu(III) system forming a stable ternary complex (LMLX-Eu(III)-MT) [65]. Therefore, in the case of both La(III) and Eu(III) it is shown that these trivalent cations can interact with these metal chelating proteins.…”
Section: Expression Analysis Of Genes Involved In General And/or Oxid...mentioning
confidence: 99%
“…In the latter study, fluorescence analysis indicates that La(III) binds to both metallothioneins via the oxygen atoms of aspartic or glutamic acid residues. A fluorimetric method for quantification of MTs is based on the use of lomefloxacin-europium(III) complex as a fluorescent probe, since MT reacts with the LMLX-Eu(III) system to form a stable ternary complex (LMLX-Eu(III)-MT) [65]. Thus, in the case of both La(III) and Eu(III), it is shown that these trivalent cations can interact with these metal chelating proteins.…”
Section: Expression Analysis Of Genes Involved In General And/or Oxid...mentioning
confidence: 99%